Implementation of Combination Vigenere Cipher and RSA in Hybrid Cryptosystem for Text Security - J Jamaludin; R Romindo (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2020)
According to the key used, cryptography can be divided into two, namely: symmetric cryptography and asymmetric cryptography, each of which has advantages and disadvantages. The selection of asymmetric cryptographic algorithm can perform the encryption process in a short time, but the key security is less secure, so it must be changed frequently. While asymmetric cryptography is the opposite, the security of key distribution can be overcome, but the data encryption process is slower. The coding process in this study uses two cryptographic algorithms, namely the Vigenere Cipher algorithm as an example of the symmetric algorithm and the RSA (Rivest Shamir Adleman) algorithm which is an example of an asymmetric algorithm. The purpose of this research is to calculate and implement so that it can be applied to overcome the weaknesses that occur from the two types of cryptography. The hybrid cryptosystem coding method is always used to overcome the weaknesses of the two cryptographs. The results show that there is an increase in security in encryption because there will be two encodings, namely message encoding with the Vigenere Cipher cryptographic algorithm and key coding with the RSA cryptographic algorithm. Besides, there is an increase in the time in the encryption and decryption process. From the results of the research, it takes 424 milliseconds in the encryption process and 335 milliseconds for the decryption process with 59,400 characters. A hybrid cryptosystem coding method using a combination of Vigenere Cipher and RSA can be implemented to increase text security and increase speed in the encryption process.